Petros Duryan in English Translations - Sharuryan, Haykanush (Bulletin of Yerevan University B: Philology, 2026)
The article examines the English translations of the poetry of the Western Armenian distinctive and prematurely deceased poet Petros Duryan (1851–1872), produced by both Armenian and American translators, which have not yet been studied by Duryan scholars at all. The study identifies the main difficulties encountered in the translation process and presents the translational value and comparative characteristics of the existing versions. It is well known that Duryan’s poetry is distinguished by its lyrical density, delicate sensitivity, sonority, and vivid imagery. Consequently, it is evident that conveying all these qualities into the target language is by no means an easy task. As a result, the study reveals frequent instances of discrepancy between form and content in the translations. The article encompasses all currently available and most comprehensive English translations of Duryan’s poetry known to readers. The theoretical framework of the research is based on Roman Jakobson’s theory of equivalence, George Steiner’s hermeneutic approach, as well as on the ideas of Susan Bassnett and other contemporary theorists, while the selection of the material is primarily aligned with the translations made by an American journalist and public figure Alice Stone Blackwell. Special attention is devoted to the semantic accuracy of the English versions and the transmission of Duryan’s distinctive lyricism. The study concludes that the most complete and faithful translation of Petros Duryan’s lyric poetry was accomplished by, a distinguished American Armenologist and professor at Harvard University James R. Russell in his voluminous collection Bosphorus Nights (2005).